2022
DOI: 10.1093/mnras/stac1046
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen reionization ends by z = 5.3: Lyman-α optical depth measured by the XQR-30 sample

Abstract: The presence of excess scatter in the Ly-α forest at z ∼ 5.5, together with the existence of sporadic extended opaque Gunn-Peterson troughs, has started to provide robust evidence for a late end of hydrogen reionization. However, low data quality and systematic uncertainties complicate the use of Ly-α transmission as a precision probe of reionization’s end stages. In this paper, we assemble a sample of 67 quasar sightlines at z > 5.5 with high signal-to-noise ratios of >10 per ≤15 km s−1 spectral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(88 citation statements)
references
References 138 publications
6
81
1
Order By: Relevance
“…A comparison between the observed Lyβ dark gap statistics for the whole sample of 42 lines of sight and predictions from multiple reionization models (Bolton et al 2017;Keating et al 2020a;Nasir & D'Aloisio 2020) confirms that evidence of reionization in the form of neutral islands and/or a fluctuating UV background persists down to at least z ∼ 5.5. This supports the conclusions in Paper I and Bosman et al (2022). In Paper I we noted a possible tension between Lyα gap statistics and a model wherein reionization ends by z < 6 but has a relatively early midpoint of z = 8.4 (Keating et al 2020a).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A comparison between the observed Lyβ dark gap statistics for the whole sample of 42 lines of sight and predictions from multiple reionization models (Bolton et al 2017;Keating et al 2020a;Nasir & D'Aloisio 2020) confirms that evidence of reionization in the form of neutral islands and/or a fluctuating UV background persists down to at least z ∼ 5.5. This supports the conclusions in Paper I and Bosman et al (2022). In Paper I we noted a possible tension between Lyα gap statistics and a model wherein reionization ends by z < 6 but has a relatively early midpoint of z = 8.4 (Keating et al 2020a).…”
Section: Discussionsupporting
confidence: 89%
“…the homogeneous-UVB model from the Sherwood Simulation Suite(Bolton et al 2017), which uses a homogeneousHaardt & Madau (2012) UV background; 2. late reionization models wherein reionization ends at z  5.3, including K20-low-τ CMB , K20-low-τ CMBhot, and K20-high-τ CMB models fromKeating et al (2020a) and ND20-late-longmfp and ND20late-shortmfp models from Nasir & D'Aloisio (2020); and 3. an early reionization model wherein the IGM is mostly ionized by z = 6 but large-scale fluctuations in the UVB, which are amplified by a short mean free path of ionizing photons (z = 5.6), persist down to lower redshifts (ND20-early-shortmfp; Nasir & D'Aloisio 2020).These models were chosen, in part, because they reproduce at least some other observations of the Lyα forest. The homogeneous-UVB model agrees well with observations at z < 5 including the IGM temperature and flux power spectra(Bolton et al 2017), although it fails to predict the Lyα opacity distribution at z > 5 (e.g.,Bosman et al 2022). The late reionization and fluctuating UVB models are broadly consistent with observations of IGM temperature, mean Lyα transmission, and fluctuations in Lyα opacity over the redshift range we…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The distributions of the measured Lyα effective optical depths τα at z > 5 are unexpectedly broad compared with the predictions of numerical simulations of the IGM. The breadths of the distributions increase with redshift, with patches of high attenuation extending over 100 h −1 comoving Mpc appearing along some lines of sight at z > 6 (Becker et al 2015(Becker et al , 2018Bosman et al 2018;Yang et al 2020;Bosman et al 2022). It has been suggested that late reionization may account for the breadths of the Lyα effective optical depth distributions, with the EoR ending as late as z 5.2 − 5.5 (Kulkarni et al 2019a;Keating et al 2020;Nasir & D'Aloisio 2020).…”
Section: Introductionmentioning
confidence: 99%